Chemical characterisation of the aroma of honeybush (Cyclopia) species - Cronje, Joan Christel (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Chemistry and Polymer Science))--University of Stellenbosch, 2010.